(Fe,Co)@nitrogen-doped graphitic carbon nanocubes derived from polydopamine-encapsulated metal–organic frameworks as a highly stable and selective non-precious oxygen reduction electrocatalyst - Xi, Jiangbo; Xia, Yating; Xu, Yangyang; Xiao, Junwu; Wang, Shuai (Chemical communications (Cambridge, England), 2015)
A facile approach is reported to synthesize (Fe,Co)@nitrogen-doped graphitic carbon (NGC) nanocubes (NCs) via the pyrolysis of polydopamine-encapsulated Fe 3 [Co(CN) 6 ] 2 NCs at 700 °C. Besides the comparable catalytic activity for oxygen reduction reaction (ORR) to the Pt/C catalyst, it showed much more outstanding catalytic selectivity and superior durability.